Strategi Pengembangan Wisata Kuliner Berbasis Masyarakat di Kabupaten Hulu Sungai Tengah - Fauzan, Muhammad Ervan; Rahmini, Noor (PPJP ULM, 2023)
This study aims to (1) Analyze how the potential of culinary tourism in District Hulu Sungai Tengah and, (2) Analyze the factors internal and external development of culinary tourism-based community in District Hulu Sungai Tengah.Respondents in this study there are 5 that is, those that affect the development of tourism in District Hulu Sungai Tengah and the culinary businesses. This study using SWOT Analysis. The results showed (1) the potential of culinary tourism in District Hulu Sungai Tengah has good potential. such as the development of typical culinary apam, lam cakes, apam barenda, layer cakes, balikuhai, pakasam, gangan humbut, bingka barandam, potato bingka, ring cakes, wadai sari india, become potential culinary tourism in Hulu Sungai Tengah Regency. The strategy of the Development of culinary tourism in District Hulu Sungai Tengah is the most appropriate strategies S-O that (2) the Development of culinary cuisine in District Hulu Sungai Tengah so many tourist who are interested in and conduct training to culinary businesses.